PENERAPAN UJI HAYATI DENGAN LEMNA SP. UNTUK MENGKAJI KUALITAS AIR SUNGAI YANG MENERIMA AIR LIMBAH INDUSTRI TEKSTIL DI KABUPATEN BANDUNG - Priyanto, Budhi (Jurnal Hidrosfir Indonesia, 2009)
To assess the possibility cause of deterioration to rice production in several villages downstream to Rancaekek, Bandung, we conducted laboratorium experiment using Lemna as the bioassay agent. Lemna sp. has been exposed to mixtures of inorganic tissue culture medium salts and filtered raw wastewater (effluent) taken from textile mill in Rancaekek, Bandung. The system was then incubated for 7 days under continuous daylight fluorescent lamps and the number of fronds and fresh weight were determined. The results show that EC50 of the textile industry’s wastewater is 37.5% of the wastewater. The LOEC value is 30% and the NOEC is 15%. This experiment suggests that wastewater from textile industry is potentially dangerous to aquatic plants, including rice and vegetable, if it was discharged to public water body without appropriate pre-treatment.